L’apport du Vsup au tour prédicatif verbo-nominal en polonais - Vetulani, Grażyna (Neophilologica, 2022)
This article is a contribution to the research on noun predication in Polish. More specifically, it focusses on the role of the support verb (Vsup) in verb-noun constructions. In this type of structure, also called verb-noun collocation, or conventionalized syntagma, the verb is collocated with an abstract noun. In this paper, Grażyna Vetulani discusses some crucial aspects of the role of the Vsup in Polish. Despite its apparently subordinated non-predicative role, the Vsup brings important semantical and grammatical information to the meaning of the whole syntagma. In particular, Vetulani argues that, it is a unifying element for the class of predicative nouns (Npréd); it indicates the register and aspect of the compound; it determines its class in the set of predicative nouns; it restricts the polysemy of the predicative noun.